2019
DOI: 10.1038/s41598-019-39335-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of postmarketing safety data for proton-pump inhibitors reveals increased propensity for renal injury, electrolyte abnormalities, and nephrolithiasis

Abstract: Proton pump inhibitors, PPIs, are widely prescribed and sold globally. Although initially intended for time-limited treatment of acute disorders, such as gastric ulcers and esophagitis, PPIs are now commonly used for prolonged durations and are considered safe for over the counter access. Recent studies have raised concern over associations between PPI use and acute kidney injury, chronic kidney disease, end-stage renal disease, and electrolyte abnormalities. The growing concern over potentially serious advers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 50 publications
0
42
0
3
Order By: Relevance
“…The primary outcome of this study was to evaluate the difference in estimated glomerular filtration rate (eGFR) calculated via Modification of Diet in Renal Disease (MDRD)-4 equation at 1 year posttransplant between patients treated with a PPI and those treated with an H2RA; this functional end point was chosen because postmarketing surveillance of PPI therapy has centered around acute and chronic kidney injury, which heretofore has not been well described in the kidney transplant population. [6][7][8][9] Renal function was also assessed at 30 days, month 3, month 6, month 9, year 3, year 5, and year 9 posttransplant. Other secondary outcomes included biopsy-proven acute rejection (BPAR), magnesium supplementation requirements, thrombocytopenia, GI effects (including gastritis, GI ulcer and GI bleeding episodes), incidence of Clostridium difficile infection, osteoporosis, fractures, and pneumonia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary outcome of this study was to evaluate the difference in estimated glomerular filtration rate (eGFR) calculated via Modification of Diet in Renal Disease (MDRD)-4 equation at 1 year posttransplant between patients treated with a PPI and those treated with an H2RA; this functional end point was chosen because postmarketing surveillance of PPI therapy has centered around acute and chronic kidney injury, which heretofore has not been well described in the kidney transplant population. [6][7][8][9] Renal function was also assessed at 30 days, month 3, month 6, month 9, year 3, year 5, and year 9 posttransplant. Other secondary outcomes included biopsy-proven acute rejection (BPAR), magnesium supplementation requirements, thrombocytopenia, GI effects (including gastritis, GI ulcer and GI bleeding episodes), incidence of Clostridium difficile infection, osteoporosis, fractures, and pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] To prevent these GI side effects, patients are prescribed acid suppression therapy with a proton pump inhibitor (PPI) or histamine-2 receptor antagonist (H2RA). Both PPIs and H2RAs have been in use for decades but recent studies have shown long-term PPI use can cause acute and chronic kidney injury, [4][5][6][7][8][9] thrombocytopenia, hypomagnesemia, hypocalcemia, and osteoporosis when compared with H2RAs. [9][10][11] Previous studies of PPI use in the kidney transplant population have mainly evaluated the shortterm risk of rejection given that PPIs reduce gastric acidity and may alter absorption and serum levels of MPA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Najnowsze doniesienia Makunts i wsp. [26] wskazują, że pacjenci, którzy stosowali preparaty IPP w monoterapii mają zwiększone ryzyko wystąpienia zarówno AKI, jak i rozwinięcia się przewlekłej choroby nerek. W swoich badaniach autorzy wykazali, że pacjenci przyjmujący omeprazol, esomeprazol, pantoprazol lub lanzoprazol w monoterapii mieli istotny wzrost częstości występowania incydentów AKI w porównaniu do osób stosujących H2-blokery.…”
Section: Schyłkowa Niewydolność Nerekunclassified
“…Publikacja wykazała statystycznie istotne 1,3-krotne zwiększenie ryzyka rozwinięcia przewlekłej choroby nerek oraz schyłkowej niewydolności nerek u pacjentów stosujących IPP, natomiast brak takiego ryzyka u pacjentów stosujących antagonistów H 2 R. Najnowsze badania Makunts i wsp. z 2019 r. [26] potwierdzają negatywny wpływ stosowania IPP na rozwój zarówno przewlekłej choroby nerek, jak i skrajnej ich niewydolności. Autorzy porównali dwie grupy pacjentów -przedstawiciele jednej z nich stosowali w monoterapii wyłącznie jeden z preparatów IPP, przedstawiciele drugiej -wybranego antagonistę receptora H 2 .…”
Section: Schyłkowa Niewydolność Nerekunclassified